Vaccine-skeptic physicians and COVID-19 vaccination rates - Andreas Steinmayr; Manuel Rossi (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
What is the role of general practitioners (GPs) in supporting or hindering public health efforts? We investigate the influence of vaccine-skeptic GPs on their patients' decisions to get a COVID-19 vaccination. We identify vaccine-skeptic GPs from the signatories of an open letter in which 199 Austrian physicians expressed their skepticism about COVID-19 vaccines. We examine small rural municipalities where patients choose a GP primarily based on geographic proximity. These vaccine-skeptic GPs reduced the vaccination rate by 5.6 percentage points. This estimate implies that they discouraged 7.9% of the vaccinable population. The effect appears to stem from discouragement rather than from rationing access to the vaccine.
Keywords: I12; I18; 330; COVID-19 vaccination; vaccine hesitancy; health policy